Customer engagement behaviour on social commerce platforms: An empirical study. (February 2021) - Busalim, Abdelsalam H.; Ghabban, Fahad; Hussin, Ab Razak Che
Abstract: Web 2.0 applications and social media have transformed e-commerce into a new business paradigm, which is called social commerce. This development has changed the customers' role and has empowered them by placing them in a unique position for influencing other buyers and providing guidance in purchasing decisions. Although a substantial amount of research has been conducted on customer behaviour, the understanding of the factors that influence customer engagement behaviour is limited, particularly in the social commerce context. This limitation is due to a lack of theoretical models for explaining such behaviour. In this study, the important factors that drive customer engagement on social commerce platforms are extracted from the literature. Drawing from social support theory, social presence theory, uses and gratifications theory, and the information system success model, we propose a new model for social commerce customer engagement. A survey-based empirical study with 203 respondents was conducted. The results demonstrated that customer engagement behaviour is strongly determined by social interaction, technological factors (interactivity and system quality), and motivational factors (hedonic and utilitarian motivations and perceived value). Among these factors, perceived value and social interaction had the most significant impacts on customer engagement behaviour on social commerce platforms. The theoretical and practical implications of the findings are discussed. Highlights: The study develops and test a customer engagement model for s-commerce platforms. Motivational factors positively effect customer engagement behaviour in s-commerce. Social interaction had positively effect on customer engagement behaviour. Perceived value was the most important factor that effect customer engagement.